2014
DOI: 10.1016/j.gene.2014.05.054
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the canine mda-7 gene, transcripts and expression patterns

Abstract: Human melanoma differentiation associated gene-7/interleukin-24 (mda-7/IL-24) displays potent growth suppressing and cell killing activity against a wide variety of human and rodent cancer cells. In this study, we identified a canine ortholog of the human mda-7/IL-24 gene located within a cluster of IL-10 family members on chromosome 7. The full-length mRNA sequence of canine mda-7 was determined, which encodes a 186-amino acid protein that has 66% similarity to human MDA-7/IL-24. Canine MDA-7 is constitutivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…FISP is shown to be expressed in Th2 cells during their differentiation, exhibits 93% and 69% amino acid similarity to rat c49a and human MDA-7, respectively, and possesses antitumor properties [ 18 , 27 ]. Sandey and colleagues studied the genomic structure and expression profile of the canine ortholog of the human mda-7/IL-24 gene and found that the mda-7 locus is evolutionarily conserved in dogs, but it has a more restrictive pattern of tissue expression than in humans [ 28 ]. Five splice variants of canine mda-7 were reported that encode four protein isoforms of the canine MDA-7.…”
Section: Identification and Structure Of Mda-7/il-24mentioning
confidence: 99%
See 2 more Smart Citations
“…FISP is shown to be expressed in Th2 cells during their differentiation, exhibits 93% and 69% amino acid similarity to rat c49a and human MDA-7, respectively, and possesses antitumor properties [ 18 , 27 ]. Sandey and colleagues studied the genomic structure and expression profile of the canine ortholog of the human mda-7/IL-24 gene and found that the mda-7 locus is evolutionarily conserved in dogs, but it has a more restrictive pattern of tissue expression than in humans [ 28 ]. Five splice variants of canine mda-7 were reported that encode four protein isoforms of the canine MDA-7.…”
Section: Identification and Structure Of Mda-7/il-24mentioning
confidence: 99%
“…Five splice variants of canine mda-7 were reported that encode four protein isoforms of the canine MDA-7. Similar to human MDA-7/IL-24, canine MDA-7 has a potential signal peptide and conserved IL-10 signature motif [ 28 ]. Due to the high amino acid sequence similarity with human MDA-7/IL-24, canine MDA-7 is also predicted to have similar antitumor properties which currently are under investigation.…”
Section: Identification and Structure Of Mda-7/il-24mentioning
confidence: 99%
See 1 more Smart Citation